EVALUASI REAKSI PESERTA PADA PENYELENGGARAAN DIKLAT DASAR JABATAN FUNGSIONAL PENYULUH PERIKANAN DI BALAI DIKLAT APARATUR KEMENTERIAN KELAUTAN DAN PERIKANAN - Nugroho, Yudistira Adi (JIV-Jurnal Ilmiah Visi, 2018)
The purpose of this study is to explain the participants reactions with Kirkpatrick model on the implementation of Basic Training of Functional Position of Fisheries Extension Workers at the Training Office for Apparatus of the Ministry of Marine Affairs and Fisheries. For research purposes, the method used in this research is the qualitative descriptive method. Instrument data collection used is the result of observation and questionnaires distributed to respondents. Data analysis using comparative techniques with scale range, that is the comparing the quality of implementation Basic Training of Functional Position Fishery`s Extension workers in expert level with Basic Training of Functional Position of Fisheries Extension Worker in proficient level. The results showed the reaction of participants using the Kirkpatrick model known that the curriculum, place of study, and dormitory in the implementation of Basic Training of Functional Position of Fisheries extension Workers in Expert Level have been very good while service of the committee, food menu, and time management still needs to be improved. For the curriculum, place of study, dormitory, service of the committee, food menu, and time management in the implementation of Basic Training of Functional Position of Fishery’s extension workers in Proficient Level still needed to be improved. References Darwin. (2017). Efektivitas kediklatan. Jakarta: Badan Pendidikan dan Pelatihan Keuangan. Febriyanti, A. (2014). Hubungan suasana lingkungan belajar dengan motivasi belajar siswa kelas V SD Negeri Gugus III Kota Bengkulu. Tesis. Bengkulu: Universitas Bengkulu. Firdaus, R, dkk. (2016). Pengaruh penataan ruang kelas terhadap hasil belajar siswa kelas V (Study eksperimen di SDN 4 Kuripan Utara) tahun 2016. Skripsi. Mataram: Universitas Mataram. Hardani, R. (2002). Pola makan sehat. Makalah Seminar Online Kharisma ke-2. Yogyakarta: RS dr. Sardjito. Ismerisa. (2013). Pengaruh pelayanan terhadap kepuasan pelanggan. Yogyakarta: UIN Sunan Kalijaga. Kirkpatrick, D. L & J.D., Kirkpatrick (2005). Evaluating training program. San Francisco, USA: Berret-Koehler Publisher, Inc. Lestari, Indah. (2013). Pengaruh waktu belajar dan minat belajar terhadap hasil belajar matematika. Jakarta: Universitas Indraprasta PGRI. Peraturan Menteri Negara Pendayagunaan AparaturNegara Nomor 19 tahun 2008 tentang Jabatan Fungsional Penyuluh Perikanan dan Angka Kreditnya. Peraturan Pemerintah Nomor 101 tahun 2000 tentang Diklat Bagi PNS. Slamet, M. (2000). Memantapkan posisi dan meningkatkan peran penyuluhan pembangunan dalam pembangunan. Prosiding Seminar IPB Bogor: Pemberdayaan Sumber Daya Manusia Menuju Terwujudnya Masyarakat Madani. Pustaka Wira Usaha Muda. Sugiarti, L. (2013). Pengaruh bahan ajar terhadap kualitas hasil belajar materi konstruksi pola pada prodi PKK tata busana. Fashion and Fashion Education Journal, 2(1), 48-54. https://journal.unnes.ac.id/sju/index.php/ffe/ article/view/2317 Undang-Undang Nomor 16 tahun 2006 tentang Sistem Penyuluhan Pertanian, Perikanan dan Kehutanan.